Moringa oleifera Use in Maintaining Oral Health and Its Potential Use in Regenerative Dentistry - Nada E. Shafiq; Anas F. Mahdee (The Scientific World Journal)
Phytomedicine refers to the use of naturally derived products to cure and mitigate human conditions. Natural products have the advantages of causing minimum side effects, being biocompatible, available, and economical, with a wide array of biological activities. Reports have described the use of natural products with antimicrobial and anti-inflammatory properties to treat oral conditions and promote wound healing. Moringa oleifera, known as the “drumstick” or “horseradish” tree, is believed to have medicinal properties regarding a range of medical conditions, though there is limited information on its use in oral medicine. This narrative review focuses on the use of Moringa extracts in the management of oral conditions, including oral infections, inflammatory conditions, the remineralization of hard tissues, oral wound healing, and tissue regeneration, drawing from both in vitro and in vivo studies which indicate that the potential of Moringa extracts in supporting dentin-pulp regeneration after caries or trauma is worthy of more careful consideration.